Fernando Pessoa’s Fausto and the concept of Subjective Tragedy - Rodrigo Alexandre Xavier (Acta Scientiarum. Language and Culture, 2016)
This paper intends to show, in an embryonic format, how Fernando Pessoa embodied the subjective process, presented in all his work through a heteronimic construction, in his writing project of Portuguese Faust. Consistent with the idea of Static Drama, Pessoa’s Fausto sights the construction of an animistic and apathetic tragedy, supported on a discursive monologism and the tragic conception of existence.